Mengembangkan Karakteristik Santri Rumah Tahfidz Al Fatihah Talang Jambe, Kota Palembang Melalui Pengajaran Al-Qur'an - Andri, ArdianMustaqiim; M. Alif Athillah; Nuraini; Nathias Amanda (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study aims to examine how the Qur'anic teaching at Rumah Tahfidz Al Fatihah, Talang Jambe, Palembang City, contributes to shaping and developing the character of students in spiritual, intellectual, social, and moral aspects. The Qur'anic learning method implemented focuses not only on memorization but also on moral development, discipline, and habitual worship. This qualitative research uses a case study approach. Data were collected through observation, interviews, and documentation. The results indicate that the Qur'anic teaching at Rumah Tahfidz Al Fatihah enhances students’ spiritual awareness, personal responsibility, and social skills. Regular recitation, memorization, review (murojaah), and the internalization of Qur’anic values are fundamental in holistically shaping students' character.